Evolusi bahasa Melayu : 2000 tahun dari zaman purba ke budaya elektronik - Mohamed Pitchay Gani Mohamed Abdul Aziz (Penerbit Universiti Pendidikan Sultan Idris, 2007)
Historical development of Malay language in Singapore from before the 7th century until the 20th century.